Comparison of effects on PBO fiber by air and oxygen dielectric barrier discharge plasma. (November 2015) - Liu, Zhe; Zeng, Qiang; Chen, Ping; Yu, Qi; Ding, Zhenfeng
Abstract: Poly(p-phenylene-2, 6-benzobisoxazole) (or PBO) fibers were treated with dielectric barrier discharge plasma (DBD) using air and oxygen gas, respectively. The treatment time was set as 12s, plasma power density of air-DBD plasma was used as 10 W/cm 3, 20 W/cm 3, 30 W/cm 3, 40 W/cm 3 and 50 W/cm 3 . The interlaminar shear strength (ILSS) between PBO fiber and bismaleimide (BMI) resin was improved by air-DBD plasma treatment and reached its highest value 57.1 MPa at 12s, 30 W/cm 3 . Meanwhile, the ILSS of PBO/BMI composites treated by oxy-DBD plasma at the same condition was only 51.2 MPa. The chemical and physical changes of PBO fiber caused by plasma were studied by X-ray photoelectron spectroscopy (XPS) and atomic force microscopy (AFM), respectively. The surface polarity and reactivity of PBO fiber were enhanced by plasma treatment, the surface was roughened as well. Otherwise, the single fiber tensile strength of PBO fibers were studied, proper parameters by plasma would not decline the mechanical property evidently. These phenomena were considered as the reason of the improved ILSS. Furthermore, the water absorption of PBO/BMI composites was tested, the composites showed good humid resistance and the plasma treatment declined the water absorption of PBO/BMI composites. Highlights: The interfacial shear strength of the PBO/BMI composites can be improved effectively by air-DBD plasma treatment. Air-DBD plasma changed the chemical compositions of PBO fiber surfaces. Air-DBD plasma roughened the PBO surfaces. The PBO/BMI composites had low water absorption.